Performance-oriented architecture and urban design: Relating information-based design and systems-thinking in architecture - Hensel, Michael Ulrich; Sørensen, Søren S. (FormAkademisk, 2019)
This article discusses a performance-oriented approach to architectural and urban design that seeks to intensify the interaction between architectures and their specific settings and environments. The overarching aim is to expand performance-oriented design in architecture to urban design and to integrate architectural, urban design and landscape design into a multi-scalar and multi-domain approach. This effort is currently comprised of three distinct research by design efforts: [i] designs for urban areas with a focus on demographic and environmental aspects, [ii] designs for peripheral areas with a focus on preserving or restoring vital local bio-physical conditions and interrelations, and [iii] designs for rural areas that elaborate an integrative approach towards constructions and correlating land uses. In order to facilitate this approach, computational information-based design is linked with systems-thinking. The portrayed research was undertaken at the Research Centre for Architecture and Tectonics and the Advanced Computational Design Laboratory at the Oslo School of Architecture and Design over a period of five years from 2014 to 2018.